Variation of Fiber Length and Specific Gravity in Wood of Cupressus sempervirens L Grown in AL-Wosaita ( AL-Jabal AL- Akhdar) Region (Albayan Scientific Journal, 2023)
This study aimed to evaluate the Italian cypress Cupressus sempervirens L wood grown in El-Jabel El-Akhdar region.The study carried out on one tree, 45 years old, growing in Al-Wasita region the selected  tree was fell as close to ground. Sampled  at different height from the base - top to study the pattern of radial variation in the fibers length and specific gravity in the distance from pith to bark and the base to top, data were analyzed using simple regression technique, Results indicated that the specific gravity values ranged between 0.558-0.811. When studying the relationship between specific gravity and cambial age, the general trend showed that the relationship was negative, that is, the value of the specific gravity decreases with the increase of the cambial age (pith to bark).While there was no clear pattern in the relationship between specific gravity and height,  with small values of  R2 ranged from 0.3 to 5.7 %.  When examining the relationship between fiber length and  the cambial age, there was a positive effect, fiber length increased radically from pith to bark.